Studio culture in architecture schools of Malaysia - Abdullah, Fadzidah; Hamedon, Siti Rohimi (2011)
In architectural education, Studio Culture is encompassed with myths that are considered necessary for architectural students to carry out in order to be successful architects. Some scholars claim that the established myths in studio culture have more bad effects to architectural students than good. The objective of this research is to investigate the influence of studio culture on architecture students particularly in Malaysia. This research uses quantitative measurement, where survey is conducted by means of distributing questionnaires to four hundreds (400) architecture students from six (6) public universities in Malaysia, and two (2) private universities. This research hypothesizes that the established studio culture has shortcomings which implicitly jeopardise the performance of architecture students in their training to become architects. By using factor analysis, this research suggests three underlying factors that summarize the general myths of studio culture namely Social Exclusion, Learning Strategies and Expense of Time. This research concludes that students do not need rules and regulation generated from myths of studio culture in order to perform properly and to be successful architects.